PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL DAN NILAI PERUSAHAAN: DAMPAK PANDEMI COVID-19 - Arif Wahyu Nur Kholid; Hadiyan Prayoga (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to examine the Institutional Ownership, Profitability and Pandemic Covid-19 on Firm Value. The population of this study are companies listed on the Indonesia Stock Exchange (IDX) 2018 - 2020. The sample selection in this study uses purposive sampling to obtain samples that represent the predetermined criteria. This research is included in quantitative research – secondary data. This research uses balance panel regression in processing the data. The estimation method used in this study is the Fixed Effect Model (FEM). The research data is processed using E-Views 10. The results of this study indicate that institutional ownership has a significant negative effect on firm value with and without the Covid-19 variable involved. However, the profitability variable has a significant positive effect on firm value when the Covid-19 variable is not included. After the Covid-19 variable is included, profitability does not have a significant effect on firm value. The implication of this research is that individual investors and the stock market are more wary of companies that have large institutional ownership and Signaling Theory can explain phenomena and test the value of companies during the COVID-19 pandemic. Future research is expected to be able to separate the types of institutional ownership by type such as banks, foundations, brokers, etc. because each type of institutional investor has different characteristics. And further research can expand the observation period and consider other factors that affect firm value.